Reviews of recent publications (Studies in 20th & 21st Century Literature, 2005)
Chanan, Michael. Cuban Cinema David William Foster Izenberg, Gerald N. Modernism and Masculinity: Mann, Wedekind, Kandisnky through World War I. Aaron J. Cohen Jonsson, Stefan. Subject Without Nation: Robert Musil and the History of Modern Identity. Post-Contemporary Interventions. Albrecht Classen Kaiser, David Aram. Romanticism, Aesthetics and Nationalism. Cambridge Studies in Romanticism 34. Catherine Grimm Lopez de Martinez, Adelaida and Harriet Turner. The Cambridge Companion to the Spanish Novel: From 1600 to the Present. Toni Dorca McCulloh, Mark R. Understanding W.G. Sebald. Peter C. Pfeiffer Peterson, Dale E. Up From Bondage: The Literatures of Russian and African American Soul. Kathleen M. Ahren
Keywords: Michael Chanan; Cuban Cinema; David William Foster; Gerald N. Izenberg; Modernism and Masculinity: Mann Wedekind Kandisnky through World War I; Aaron J. Cohen; Stefan Jonsson; Subject Without Nation: Robert Musil and the History of Modern Identity; Post-Contemporary Interventions; Albrecht Classen; David Aram Kaiser; Romanticism Aesthetics and Nationalism; Cambridge Studies in Romanticism 34; Catherine Grimm; Adelaida Lopez de Martinez; Harriet Turner; The Cambridge Companion to the Spanish Novel: From 1600 to the Present; Toni Dorca; Mark R. McCulloh; Understanding W.G. Sebald; Peter C. Pfeiffer; Dale E. Peterson; Up From Bondage: The Literatures of Russian and African American Soul; Kathleen M. Ahren